2011
DOI: 10.1007/s00285-011-0428-2
|View full text |Cite
|
Sign up to set email alerts
|

A non-negative matrix factorization framework for identifying modular patterns in metagenomic profile data

Abstract: Metagenomic studies sequence DNA directly from environmental samples to explore the structure and function of complex microbial and viral communities. Individual, short pieces of sequenced DNA ("reads") are classified into (putative) taxonomic or metabolic groups which are analyzed for patterns across samples. Analysis of such read matrices is at the core of using metagenomic data to make inferences about ecosystem structure and function. Non-negative matrix factorization (NMF) is a numerical technique for app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 43 publications
0
21
0
Order By: Relevance
“…We applied a concordance method (see Materials and Methods and [26]) to compare possible decomposition ranks, and found that 5 is a suitable rank for the NMF decomposition of the GOS data (Figure 1 in Text S1). This means that the observed Pfam profile matrix () can be stably approximated using 5 functional profiles and associated site profiles.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We applied a concordance method (see Materials and Methods and [26]) to compare possible decomposition ranks, and found that 5 is a suitable rank for the NMF decomposition of the GOS data (Figure 1 in Text S1). This means that the observed Pfam profile matrix () can be stably approximated using 5 functional profiles and associated site profiles.…”
Section: Resultsmentioning
confidence: 99%
“…We applied NMF on the whole Pfam profile and we selected Pfams based on the correlation between their spatial distribution and the site profile of each component (Figure 3a). We contend that this correlation-based approach is preferable to “specificity-” [26] or “projection-” [27], [28] based methods, because it avoids undue bias toward either rare or ubiquitous Pfams (see Materials and Methods and Figure 4 in Text S1). …”
Section: Resultsmentioning
confidence: 99%
“…Parameter selection procedures proposed in most applications of NMF to biological data are based upon stability of the weight matrix W over several initializations of the iterative algorithm used to solve the problem [12, 13, 15, 16], in particular regarding the clustering of samples. Since our use of NMF focuses on extracting reproducible biological mechanisms characterized by the trait matrix H , we are more interested in biological stability than numerical one.…”
Section: Resultsmentioning
confidence: 99%
“…As mentioned in the introduction, NMF techniques were previously used as a “soft” clustering tool to compare samples from various ecosystems, ranging from marine environment to human body ([15, 16], [17]). However, our work focused on different aspects of NMF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation